2017
DOI: 10.1542/peds.2017-0988
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment of HIV-Exposed and HIV-Unexposed Uninfected Children at 24 Months

Abstract: HEU children performed equally well on neurodevelopmental assessments at 24 months of age compared with HUU children. Given the global expansion of the HEU population, results suggesting no adverse impact of in-utero HIV and antiretroviral exposure on early neurodevelopment are reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 31 publications
(23 reference statements)
10
85
0
Order By: Relevance
“…Two of the largest studies from southern Africa used the Bayley Scales of Infant and Toddler Development and had conflicting findings. In Botswana, between 2010 and 2012 when only one‐third of mothers received combination ART during pregnancy and <10% of CHEU were breastfed compared to >99% of CHU, there was little evidence of differences in neurodevelopment at 24 months of age (N = 724) . However, in the era of combination maternal ART and breastfeeding in South Africa, CHEU had higher odds of cognitive and motor, although not language, delay at 13 months of age (N = 521) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the largest studies from southern Africa used the Bayley Scales of Infant and Toddler Development and had conflicting findings. In Botswana, between 2010 and 2012 when only one‐third of mothers received combination ART during pregnancy and <10% of CHEU were breastfed compared to >99% of CHU, there was little evidence of differences in neurodevelopment at 24 months of age (N = 724) . However, in the era of combination maternal ART and breastfeeding in South Africa, CHEU had higher odds of cognitive and motor, although not language, delay at 13 months of age (N = 521) .…”
Section: Discussionmentioning
confidence: 99%
“…At 12 months of age, a study from South Africa found increased odds of cognitive and motor delay . At two years of age, a study from Botswana showed expressive language delay and a study from South Africa found receptive and expressive language delay . In contrast, a study from Uganda and Malawi did not find difference in neurodevelopmental outcomes in CHEU compared to CHU aged one to five years .…”
Section: Introductionmentioning
confidence: 91%
“…For both zidovudine‐ and lamuvidine‐exposed rodents, some studies suggested that memory and learning may be impaired at early ages . More recent clinical studies with newer ART regimens have not found such deficits in young children . Fewer data are available about specific cognitive functions in older HEU children and adolescents, but studies have found a higher frequency of reading and math impairments in HEU children compared to the general population .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis on neurodevelopment in HIV‐exposed uninfected (HEU) children highlighted the limitations in the current body of literature including the heterogeneity of the patient populations between studies, limited confounders measured and variability in ART regimens. More recent studies are often limited by sample size and have mixed results .…”
Section: Introductionmentioning
confidence: 99%
“…[47] A recent study from SA found motor and cognitive delay, particularly associated with preterm birth, [51] and a study from Zambia reported a later impact on school performance. [52] However, other studies in Botswana [53] and SA [54] have not found substantial differences when compared with HIV-unexposed children, although some language impairment was demonstrated, which has also been seen in high-income settings. [55] Further research and follow-up of both CLHIV and HEU children in the current ART era is needed to determine the nature of the developmental delay as well as the long-term implications.…”
Section: Early Neurodevelopmentmentioning
confidence: 83%